MONITORING SISTEM ENERGY LIMITER BERBASIS INTERNET OF THINGS - Alfith, Alfith; Effendi, Asnal; Bachtiar, Antonov; Premadi, Aswir (Ensiklopedia of Journal, 2024)
Solar power plants generate a source of direct current voltage. Then, the source of reverse voltage is generated using an inverter. The results of this study show that the specimen can be observed and controlled for 24 hours through a website through the Internet of Things technology. (IoT). It was designed using ESP266 to function as a kWh meter and is equipped with a monitoring and remote-control module. With a 220 Ω barrier value as a barrier variable, the operational reinforcement test series on the photovoltaic surveillance system has an accuracy of 97.34%. The maximum voltage generated is 225 V, with a photovoltic output at a current of 0.8 A and a minimum voltage of 185 V, so the current value is 0.7 A.Keywords: ESP8266, Internet of Things, Photovoltaic, Op-Amp